Estudo do acesso à justiça na perspectiva do abuso do direito de litigar: a análise econômica dos planos de saúde na qualidade de litigantes habituais - Santiago, Hiasmine (2022)
The role of the Brazilian Judiciary has been studied for a long time by the doctrine, notably due to the inability to provide adequate, fair and timely legal protection to society, with numerous discussions about the causes of this phenomenon, among which habitual litigation stands out. The identification of this category of litigant is imperative to define why it is more relevant to remain with the litigious behavior and, by methodological approach, one must analyze the situation of health plans, which deal with the most important right of the human being: the Right to life. The objective of the present work is to trace the paths through which the behavior of this category permeates, in the light of Economic Analysis of Law, a science that provides the law with a theoretical instrument of economic matrices, in order to analyze human behavior in an efficient way. From the hypothetical-deductive method of approach, with explanatory purpose and use of bibliographic and documentary research techniques, it was concluded that there are still some advantages justified by economic science to the usual litigant who keep using the justice system for breaching their contracts in order to have a positive impact on the numerical crisis of the judiciary.